HDAC9 gene is associated with stroke risk in a Chinese population. (July 2013) - Han, Yan; Sun, Wenzhu; Wang, Li; Tao, Sha; Tian, Lu; Hao, Yong; Zhang, Wei; Wu, Shuai; Li, Shixu; Lv, Huihui; Zheng, S Lilly; Sun, Jielin; et al.
A recent Genome-Wide Association study (GWAS) identified rs11984041 on HDAC9 gene to be significantly associated with stroke in a Caucasian population. However, whether HDAC9 gene also plays a role in other ethnicities is unknown. The current study was conducted to investigate the association of single nucleotide polymorphisms (SNPs) on HDAC9 gene and stroke risk in a Chinese population. Sixteen tagging SNPs for HDAC9 gene were genotyped in a Chinese population of 279 stroke cases and 984 controls from Changhai Hospital in Shanghai, China. The candidate region of HDAC9 investigated was on a haplotype block located between two recombination hotspots in the tail region of HDAC9, the only region harbouring significantly associated SNPs based on the previous GWAS. rs11984041 was not polymorphic in Chinese population. Two other SNPs, rs2389995 and rs2240419 on HDAC9 of chromosome 7q21.1, were significantly associated with large-vessel stroke risk, with P values of 0.035 and 0.042, respectively (Table 3 ). Individuals with risk allele (A) for rs2389995 and (T) for rs2240419 had increased risk of stroke (odds ratio [OR] = 1.33, 95% confidence interval [CI]: 1.01–1.75; and OR = 1.29, 95% CI: 1.02–1.63), respectively. Multivariate analysis including both SNPs in the logistic regression model revealed independent association effects of each SNP, with a P = 0.013 and 0.010, respectively. The results from our studies indicate HDAC9 gene is significantly associated with large-vessel stroke risk in Chinese population. However, SNPs on HDAC9 gene display heterogeneity effects across different ethnic populations. Additional studies are needed to further evaluate our results.